A novel technique for digital image watermarking in spatial domain - Singh A.K.; Sharma N.; Dave M.; Mohan A. (My University, 2025)
Information technology has eased the duplication, manipulation and distribution of digital data in recent times which has resulted in the demand for safe ownership of digital images. A very crucial concern for the content owners and distributors is copyright protection and content authentication. The solution to these problems is Digital Watermarking. The watermarking is the process of embedding a signal in to other signal robustly and invisibly at the same time, the embedded signal is called watermark and the other signal is called cover or host signal. In this paper we presents a brief overview of digital image watermarking techniques in spatial and frequency domain, proposed a watermarking algorithm in spatial domain by using the Least Significant Bit (LSB) method. Every technique has some advantages and disadvantages but the LSB method is to very good compromise between performance, robustness, computational cost and quality of embedding. © 2012 IEEE.